An Exploratory Study of How Older Cubans Cope with Difficult Living Conditions. (1st April 2019) - Strug, David L.
Abstract : Population aging is a concern to policy makers in Cuba where by 2025 there will be more pensioners than workers. We describe a unique, exploratory study of older Cubans 60+ years of age and how they cope with stress associated with economic vulnerability and adverse living conditions. Many older persons have incomes too low to provide a minimum standard of living. We address the following questions. (1) What chronic environmental stressors do older persons face? (2) What strategies do they employ to cope with these stressors? (3) What implications for policy follow from these questions? We discuss qualitative data from interviews with 50 older persons conducted in Havana in a mixed methods investigation. Most participants appraised difficult living conditions as hard to change, which explains a high prevalence of the use of avoidance coping strategies, including resignation. Policy makers need to understand how older persons cope with adversity to determine relevant service needs for this population.